Faktor-faktor yang Mempengaruhi Laba Bersih: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Aneka Industri yang Terdaftar pada Bursa Efek Indonesia Periode 2019 – 2023 - Hasna Syifa Salsabila; Melan Sinaga (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The purpose of the study is to determine and analyze the effect of Operating Cost, Sales, Cash Turnover, Receivable Turnover, and Inventory Turnover on Net Income of Various Industrial sub sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2019- 2023. In this study, a purposive sampling method is used, which obtained 37 companies. The data analysis used in this study is multiple linear regression analysis using SPSS software version 22 and Microsoft Excel 2019. The results of this study indicate that Operating Cost and Cash Turnover has no effect on Net Income. At the same time, sales have negative significant effect on Net Income, Receivable Turnover have negative significant effect on Net Income, and Inventory Turnover have positive significant effect on Net Income.